Poor sleep quality in post menopause woman - Thalia Wiranda; Andriana Kumala Dewi (Science Midwifery, 2023)
Generally, women after having menopause are less satisfied with their sleep and as many 61% report insomnia symptoms. Sleep quality is an important constituent and an essential part of someone`s quality of life. The worsening quality of sleep in women after having menopause is affected by several factors, such as age, marital status, history of hypertension, and BMI status. This research aims to find out the depiction of grievances and sleep quality in women after having menopause in Panti Werdha Wisma Mulia and Panti Werdha Berea, West Jakarta. This is descriptive research that was conducted on December 23rd at Panti Werdha Wisma Mulia and Panti Werdha Berea West Jakarta, with the sampling was 44 women. PSQI was the instrument used to get the depiction of sleep quality. The result of the research showed that there are 40 respondents (90,91%) that have bad sleep quality while only 4 people (9, 09%) who have good sleep quality.